Gender specification of Polish nouns naming people: language system and public debate arguments - Agnieszka Kiełkiewicz-Janowiak (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave, 2019)
Changes in language practices take place against a backdrop of social pressures for greater gender equality. The topic of the current paper concerns the grammatical and social complexities of a language reform for gender fair representation in the Polish context. The “socially-motivated” language reform, which aims to enhance social equality, is underpinned but also challenged by the language systemon the one hand and by public debate on the other. Therefore, grammatical constraints afforded by the language system need to be investigated in the context of the social attitudes to gender relations in Poland as well as attitudes to the proposed linguistic innovations. It is our aim here to reflect upon the current social debate about the process of ongoing language change, more specifically to consider the relevant linguistic and social arguments. These arguments used are discussed, as revealed in a close analysis of a range of texts of varying genre, social reach and significance, written as a reaction to usage dilemmas often faced by the speakers. The texts were collected between January 2014 and November 2019.  The paper concludes with suggestions of the best policy to deal with a highly controversial socio-linguistic issue.